The school of rock: Sergei Solov'ev's workshop and its legacy for the popular music film. (4th May 2019) - Safariants, Rita
ABSTRACT: Part of a special issue devoted to the centenary of the Film Institute VGIK, this article considers the significant role that the VGIK played in nurturing the production networks responsible for the vast majority of rock-music-themed films in Soviet and post-Soviet Russia. When viewed from the perspective of academic preparation, mentorship and film production opportunities for aspiring filmmakers, VGIK begins to resemble a veritable 'film school of rock' in its enduring support of student and faculty projects that focus on underground rock-and-roll culture. Drawing on coursework films and production histories, as well as the thematic and stylistic profiles of both staff and student film-makers, this article addresses the role and legacy of popular music in shaping the curricular practices and interpersonal networks at Russia's most prestigious film school.